Binge-watching como um novo modo de assistir televisão : uma análise comparativa entre o fenômeno em arquivo e em fluxo - Cardoso, Jéferson Cristiano Cortes Zambom (2017)
This dissertation analyzes the phenomenon called binge-watching and how this new way of watching television is changing the behavior of viewers who come to play roles of users, hiperviewers and multipliers. For this was done an anlytical in two stages. In the first was done an monitoring, measurement and analysis of the comments of this public on Twitter before, during and after the launch of sitcom Orange Is The New Black (OITNB), production of Netflix, in addition to posts in Brazilian official accounts (@OITNBrazil) and American (@OITNB) to check public behavior in these spaces. In the second stage was done an monitoring, measurement and analysis of the comments of this public on Twitter before, during and after an marathon simulation, in the pay television, of sitcom The Walking Dead (TWD), production of AMC, displayed by Fox, in addition to posts in Brazilian official accounts (@TWDBrasil) and American (@WalkingDead_AMC), to see what changes when the binge-watching is spontaneous, occurring in a file environment, in which one can determine when will be marathon or not, or when the binge-watching is induced, occurring in a flow environment in which the viewer can not determine when it will do the marathon, can only choose whether to follow what it is being broadcast on television or not. It was contacted that the official accounts are restricted to participation of moderators and in Brazil the public does not use the term binge-watching, but marathon, watching the series mainly on launch day, when in file, and not having a strong attachment to the simulations. To support this research were used authors as Jenkins (2009), Kinder, (1991), Cannito (2010), Bauman (2008/2009/2013), Anderson (2006), Jenkins, Green and Ford (2014), Lipovetsky and Serroy (2012), Johnson (2012), Shirky (2011), Scolari (2014), Mattos (2013), Negroponte (1995), Eco (1986), Foucault (2002), Wolton (1996) and McLuhan (1979).. The methodology used was the Depth Hermeneutics as Thompson's vision (1995), using as technique of structuring data collection Bardin's Content Analysis (2011) and the analysis of data Computer Discourse Mediated Analysis (CDMA ) Herring (2004).